2010
DOI: 10.1007/978-3-642-12002-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Satisfiability Modulo the Theory of Costs: Foundations and Applications

Abstract: Abstract. We extend the setting of Satisfiability Modulo Theories (SMT) by introducing a theory of costs C, where it is possible to model and reason about resource consumption and multiple cost functions, e.g., battery, time, and space. We define a decision procedure that has all the features required for the integration withint the lazy SMT schema: incrementality, backtrackability, construction of conflict sets, and deduction. This naturally results in an SMT solver for the disjoint union of C and any other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 9 publications
0
65
0
Order By: Relevance
“…In [17], Cimatti et al proposed a theory of costs for augmenting an SMT solver with pseudo-boolean (PB) constraints [9]. At a high level, their theory allows associating a cost with individual Boolean constraints.…”
Section: Related Workmentioning
confidence: 99%
“…In [17], Cimatti et al proposed a theory of costs for augmenting an SMT solver with pseudo-boolean (PB) constraints [9]. At a high level, their theory allows associating a cost with individual Boolean constraints.…”
Section: Related Workmentioning
confidence: 99%
“…In 2010, Cimatti et al [6] proposed a new theory called the theory of Costs C that allows modeling multiple cost functions, and they developed a decision procedure for C. Using the theory C, Cimatti et al [6] showed how to address the problem of minimizing the value of one cost function subject to the satisfaction of a SMT(T ) formula, which they called the Boolean Optimization Modulo Theory (BOMT) problem. The optimization itself is obtained by linear search or binary search, asserting atoms of C that bound the cost, and using an incremental SMT solver.…”
Section: Algorithmmentioning
confidence: 99%
“…The optimization itself is obtained by linear search or binary search, asserting atoms of C that bound the cost, and using an incremental SMT solver. Cimatti et al [6] encoded the weighted partial MaxSMT into BOMT by adding a new Boolean variable A i j to each soft clause. Then, the cost function is the sum of the weights of the soft clauses, whose variable A i j is assigned true.…”
Section: Algorithmmentioning
confidence: 99%
“…We propose heuristics for guiding the domain relaxation step by means of the analysis of minimal models generated by the SMT(LIA) solver. More specifically, we consider two different cost functions: first, the number of violated artificial domain bounds, which leads to Maximum Satisfiability Modulo Theories (Max-SMT, [28,29]) problems; and second, the distance with respect to the artificial domains, which boils down to Optimization Modulo Theories (OMT, [30,31]) problems. The results of comparing these approaches with other techniques show the potential of the method.…”
Section: Introductionmentioning
confidence: 99%